2023
DOI: 10.1186/s12917-023-03598-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus pumilus TS1 alleviates Salmonella Enteritidis-induced intestinal injury in broilers

Abstract: Background In the current context of reduced and limited antibiotic use, several pathogens and stressors cause intestinal oxidative stress in poultry, which leads to a reduced feed intake, slow or stagnant growth and development, and even death, resulting in huge economic losses to the poultry breeding industry. Oxidative stress in animals is a non-specific injury for which no targeted drug therapy is available; however, the health of poultry can be improved by adding appropriate feed additives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The SE infection reduced the villus height and the villus to crypt ratio in both the duodenum and jejunum. This result is similar to those found by Moharreri et al (2022) and Liu et al (2023), who identified significant morphological changes in the ileum and jejunum portions, respectively, in birds challenged with SE. In oral infection, Salmonella promotes an influx of heterophils and monocytic phagocytes, which results in damage including fusion and shortening of villi and damage of follicleassociated epithelium (Iqbal et al, 2005;Wigley, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SE infection reduced the villus height and the villus to crypt ratio in both the duodenum and jejunum. This result is similar to those found by Moharreri et al (2022) and Liu et al (2023), who identified significant morphological changes in the ileum and jejunum portions, respectively, in birds challenged with SE. In oral infection, Salmonella promotes an influx of heterophils and monocytic phagocytes, which results in damage including fusion and shortening of villi and damage of follicleassociated epithelium (Iqbal et al, 2005;Wigley, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In oral infection, Salmonella promotes an influx of heterophils and monocytic phagocytes, which results in damage including fusion and shortening of villi and damage of follicleassociated epithelium (Iqbal et al, 2005;Wigley, 2014). The overproduction of reactive oxygen species caused by SE can also cause damage to epithelial cells and other histopathological changes (Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species, 1 type of beneficial bacteria in the animal intestine, has been widely used for promoting growth performance and improving intestinal health under normal and pathogens challenge ( Kan et al, 2021 ; Xu et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2023 ). Moreover, in the last decades, advanced-progresses of Bacillus species have been achieved in broiler chickens ( Manafi et al, 2018 ; Chang and Yu, 2022 ; Lena et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%